Adsorption of Cellulase Isolated from on Chitosan/Alginate Particles Functionalized with Epichlorohydrin - Elaine C. Rodrigues; Bruna T. C. Bezerra; Barbara V. Farias; Wellington S. Adriano; Rodrigo S. Vieira; Diana C. S. Azevedo; Ivanildo J. Silva (Adsorption Science & Technology)
This work investigates the adsorption of cellulase (isolated from Aspergillus niger ) in a fixed-bed column using chitosan/alginate particles functionalized with epichlorohydrin (Cs/Ag–E) as the adsorbent. The particles were prepared and characterized with respect to apparent density, particle porosity, particle size, surface chemistry and thermal stability. Cellulase solutions were prepared in sodium citrate buffer (20 mM) at pH 5. Several breakthrough curves were obtained by varying the flow rate and feed concentrations in order to evaluate the suitable bed height and determine the adsorption isotherm, respectively. The adsorption isotherm fitted well with Langmuir equation with maximum adsorption capacity of about 11 mg of cellulase/g of adsorbent. Successive cycles (adsorption/washing/elution) were performed and the results demonstrate the reversibility of the process and its potential for enzyme purification and separation. However, cellulase activity in the eluted fraction is only 29% of that of the fresh enzyme fed to the column.